Bengal in the sixteenth century A.D. - Das Gupta, J. N. (Calcutta : University of Calcutta, 1914)
On the social and economic conditions of Bengal, India.
Microfilm.
Keywords: Bengal (India) -- Social conditions; Bengal (India) -- Economic conditions